Hyaluronic Acid-based Biomimetic Hydrogels for Tissue Engineering and Medical Applications - An, Soohwan; Choi, Soojeong; Min, Sungjin; Cho, Seung-Woo (Biotechnology and bioprocess engineering, 2021)
Hyaluronic acid (HA), an essential component of extracellular matrix (ECM), plays an important role in various cellular activities, including migration, proliferation, and differentiation. Not only its structural and biological properties, but also properties such as biocompatibility, biodegradability, and low immunogenicity make HA a promising biomaterial for tissue engineering and regenerative medicine. HA has been widely utilized as a hydrogel to form complex polymer networks, which can be chemically modified owing to the abundance of functional groups. To closely recapitulate native tissues, many approaches have been developed through chemical modification, incorporation of various biomaterials and biomolecules based on biomimetics, and fabrication techniques. Thus, HA-based hydrogels can be designed to exhibit specific properties or functions for targeted tissues, capable of maintaining or replacing structural and biological properties. This review highlights recent efforts in developing HA-based hydrogels as ECM-mimetic scaffolds and bio-inspired functional biomaterials in the fields of tissue engineering and regenerative medicine as well as their medical applications.